2022
DOI: 10.1029/2021jd035438
|View full text |Cite
|
Sign up to set email alerts
|

Satellite Observed Sensitivity of Tropical Clouds and Moisture to Sea Surface Temperature on Various Time and Space Scales: 1. Focus on High Level Cloud Situations Over Ocean

Abstract: This study examines variations in high cloud properties and relative humidity (RH) with sea surface temperature (SST) over tropical oceans (30°N–30°S) using spaceborne lidar and microwave radiometer observations. The mean values over the tropics indicate that middle‐tropospheric RH increases, high cloud covers decrease and cloud altitudes rise with SST. These signatures are consistent with the hypotheses proposed in the literature. The analysis of this same data set but at the scale of local processes shows di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 104 publications
2
2
0
Order By: Relevance
“…Using CALIPSO satellite observations, we showed that tropical high clouds are rising. This builds on several recent studies that also found a rise in tropical high clouds using passive and active sensors as well as studies that projected their upward shift associated with warming (Aerenson et al, 2022;Chepfer et al, 2014;Höjgård-Olsen et al, 2022;Norris et al, 2016;Richardson et al, 2022;Saint-Lu et al, 2020;Takahashi et al, 2019). We show that this surface warming-induced rise elicits a vertical dipole in cloud cover, consistent with the FAT mechanism.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Using CALIPSO satellite observations, we showed that tropical high clouds are rising. This builds on several recent studies that also found a rise in tropical high clouds using passive and active sensors as well as studies that projected their upward shift associated with warming (Aerenson et al, 2022;Chepfer et al, 2014;Höjgård-Olsen et al, 2022;Norris et al, 2016;Richardson et al, 2022;Saint-Lu et al, 2020;Takahashi et al, 2019). We show that this surface warming-induced rise elicits a vertical dipole in cloud cover, consistent with the FAT mechanism.…”
Section: Conclusion and Discussionsupporting
confidence: 84%
“…Most studies, supported by modeling and theory, suggest a decrease with warming albeit without consensus on magnitude (e.g., Beydoun et al., 2021; Bony et al., 2016; Wing et al., 2020; Zelinka & Hartmann, 2010). Only a few studies have brought observations to bear on this particular problem (Chepfer et al., 2014; Del Genio et al., 2005; Höjgård‐Olsen et al., 2022; Igel et al., 2014; Saint‐Lu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…7), demonstrating that this thinning can occur regardless of whether f ice increases, decreases, or stays the same. The thinning is qualitatively consistent with recent observational and model-based analyses [8,16,21,39,40].…”
Section: Ice Cloud Thinning In Response To Warmingsupporting
confidence: 89%
“…Observational studies have confirmed altitude shifts of clouds in response to warmer temperatures based on interannual climate variability [39][40][41][42], while first evidence for long-term shift trends is also emerging from the climatic variability [43]. These findings suggest that the altitude-driven CRH change may already influence the role of high clouds in the climate system beyond their role in interannual variability.…”
Section: Summary and Implicationsmentioning
confidence: 84%